A Survey of Performance Comparison between Virtual Machines and Containers - Desai, Prashant Ramchandra (International Journal of Computer Sciences and Engineering, 2025)
Since the onset of Cloud computing and its inroads into infrastructure as a service, Virtualization has become peak of importance in the field of abstraction and resource management. However, these additional layers of abstraction provided by virtualization come at a trade-off between performance and cost in a cloud environment where everything is on a pay-per-use basis. Containers which are perceived to be the future of virtualization are developed to address these issues. This study paper scrutinizes the performance of a conventional virtual machine and contrasts them with the containers. We cover the critical assessment of each parameter and its behavior when its subjected to various stress tests. We discuss the implementations and their performance metrics to help us draw conclusions on which one is ideal to use for desired needs. After assessment of the result and discussion of the limitations, we conclude with prospects for future research.